Examination and Analysis of the Status of Islamic jurisprudence and Compliance with Laws in Secular Islamic and Non-Islamic Countries - Musavisadat, Zeynab (Legal Studies in Digital Age, 2025)
This study examines and analyzes the status of Islamic jurisprudence (fiqh) in its encounter with civil laws in secular Islamic countries and secular non-Islamic countries. The central research question is how Islamic jurisprudence can coexist with secular structures and what opportunities and challenges exist in this process. The research method is designed as qualitative, analytical, and comparative, and data were collected through the analysis of jurisprudential texts, national constitutions, legal documents, and contemporary studies. The findings indicate that in secular Islamic countries, Islamic jurisprudence often faces structural constraints at the institutional level, and its role has been reduced to areas such as personal status law, although in some contexts such as Indonesia, more flexible models of coexistence between Sharia and Secularism are observed. In contrast, in secular non-Islamic countries, Islamic jurisprudence plays a role primarily at the social and informal institutional levels through Sharia councils and private arbitration bodies. Although limitations remain in the areas of religious freedoms, women’s rights, and gender equality, the relative acceptance of legal pluralism and the emergence of the concept of Fiqh al-Aqalliyyat (“jurisprudence of minorities”) has created an important opportunity for coexistence. The main conclusion of this research is that the interaction between Islamic jurisprudence and secularism is a dynamic and historical process that is neither entirely confrontational nor entirely accommodative but instead encompasses a spectrum of legal coexistence. This study introduces its theoretical innovation through the concept of “dynamic legal coexistence” and demonstrates that the success of this coexistence depends on two fundamental factors: the ijtihadi capacity of Islamic jurisprudence to reinterpret legal rulings and the degree of openness of secular systems in accepting legal pluralism. Accordingly, it is suggested that jurisprudential institutions, secular governments, and international organizations collaborate simultaneously to develop sustainable models of legal interaction.